Relationship of Anxiety, Inflammation, and Telomere Length in Postpartum Women: A Pilot Study. Issue 2 (April 2020) - Groer, Maureen; Louis-Jacques, Adetola; Szalacha, Laura; Redwine, Laura; Dracxler, Roberta; Keefe, David
Background: The postpartum period can be a vulnerable time during which many women are prone to mood disturbances. Since telomere length (TL) is known to be associated with dysphoric moods, inflammation, and stress in many populations, this study's objective was to assess the relationships among TL, dysphoric moods, stress, and inflammation during the postpartum period. Method: This cross-sectional pilot study is a secondary analysis of data collected in a larger parent study of anti-thyroid peroxidase (TPO) enzyme antibody positive versus negative women. The parent study followed selected mothers every month for 6 postpartum months. From this parent study, a random sample of preserved peripheral blood mononuclear cells from 97 participants collected at 2–4 months postpartum were measured for TL. Data were available on the production of interleukin-6 (IL-6), an inflammatory cytokine, in stimulated ex vivo cultures for 59 of these women. Dysphoric moods and stress were measured. Pearson correlations and linear regressions were performed, controlling for postpartum thyroiditis status and age. Results: There were no statistically significant relationships between TL and demographic factors, stress, depression, or TPO status. There were significant negative correlations between TL and anxiety and a trend for a relationship between TL and IL-6 levels. IL-6 levels were significantly, positively associated with negative moods. Conclusions: Higher anxiety scores and inflammation were associated with shorter TL. Inflammation was related to anxiety and other dysphoric moods and was marginally associated with shorter TLs.